Minority status, stigma, prejudice and bullying: growing up in jeopardy. (August 2021) - Skuse, David
Abstract : Stigma and alienation are suffered by many individuals with mental health disorders, in societies around the world. Rejection is all the more common among those who have intellectual disabilities or who are from ethnic minorities. In this issue, three papers consider the suffering experienced by patients with vulnerabilities that militate against their being in receipt of the psychiatric care they assuredly deserve.